Remaking Political Institutions: Climate Change and Beyond - Patterson, James J. (Physical Sciences, 2020)
This Element develops an original analytical foundation for studying institutional remaking and its political dynamics. It explains how institutional remaking can be observed and provides a typology comprising five areas of institutional production involved in institutional remaking (Novelty, Uptake, Dismantling, Stability, Interplay).